Public investment a key prerequisite for private sector activity - Marius Clemens; Marius Goerge; Claus Michelsen (DIW Weekly Report, 2019)
Ten years after the 2008 financial crisis, in the euro area investment is still below the pre-crisis level. Public and private investment growth is so weak that capital per worker (capital intensity) has virtually remained constant. An increase in public investment activity could ultimately stimulate private investment. Estimates for the euro area show that an increase in public investment by one billion euro goes hand in hand with a medium-term increase in private investment of around 1.1 billion euro. In Germany, the effect is somewhat greater. Investment in construction and infrastructure are the most significant drivers. The public sector's widespread reluctance to invest could partially explain the weakness in private investment activity. The public sector should now begin investing more. And the rigid balanced budget amendment (Schuldenbremse) should be replaced by more flexible expenditure rules.
Keywords: E22; E62; H54; 330; investment; crowding in; public finance